Планета Земля: справочное издание / Г. М. Абакумова [и др.] - Абакумова Г. М. (Детская энциклопедия РОСМЭН, 2013)
Экземпляры: (20160120) / Инвентарный номер: 1039 / Цена: / Сис.шифр: 26.0я2 / Авт.знак: П 37 / ББК: 26.0я2